Biological characteristics, feeding and structure of tunnels of the greater mole-rat (Spalax microphthalmus) in the area of the regional landscape park “Velikoburlutskyi Steppe” - Tokarskaya, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
New data on the greater mole-rat’s biology in the territory of the Regional landscape park «Velikoburlutskyi steppe” (Kharkiv region, Ukraine) concerning nutrition, burrow structure and social structure are presented. The greater mole-rat has only one litter consisting of 1–3 pups during the year. Contrary to the prevailing general opinion that mole-rats lead solitary way of life we have found cohabitation of a female, a male and their young of the current year at three of the seven areas of our study. Young mole-rats settle in a new place at the end of June – early July. They can be found above ground often at this time. In the greater mole-rat population from the Regional Park “Velikoburlutskyi steppe” males are characterized by the body length of 220–260 mm, by hind foot length of 27–30 mm, by the body weight of 219–520 g. For adult females the average body length is 200–250 mm, the hind foot length is about 26–30 mm, the body weight ranges from 284 to 409.6 g. Many greater mole-rat specimens on the forehead or occiput have an individual light spot (yellowish-white) or a white longitudinal strip by which we can identify individuals at repeated catching. Eating the underground parts of plants, the mole-rat makes very long tunnels conducting by them horizontally and closely to the surface and throwing along them the large piles of soil (up to 0.5 m in diameter). Soil emissions marking feeding tunnels had a base diameter of up to 50–60 cm. In the nest part of the hole the number of habitable chambers and chambers for stocks can be up to 10, and they are located at the depth of 3.5 m. Digging activity of the mole-rat grows in late March – early April and in the autumn at the end of September – early October. We have repeatedly noted the appearance of emissions in the winter during the thaw. Mole-rats harm the agriculture with their digging activity (damage cultivated areas, digging under the plants and so on); in addition, mole-rats sometimes directly eat potato tubers, onion and other root vegetables. The total weight of one mole-rat stock can reach 16 kg. In one of burrows excavated by us near the vegetable gardens of locals in Nesterivka village of Velikoburlukskyi district in Kharkiv region we found 8 kg of potatoes, 4 kg of carrots, 3 kg of greater burdock roots, 0.6 kg of couch grass roots.